Penetration of UV‐visible solar radiation in the global oceans: Insights from ocean color remote sensing. Issue 9 (5th September 2013) - Lee, Zhongping; Hu, Chuanmin; Shang, Shaoling; Du, Keping; Lewis, Marlon; Arnone, Robert; Brewin, Robert
<x xml:space="preserve">Abstract</x> [1] Penetration of solar radiation in the ocean is determined by the attenuation coefficient (Kd(λ)). Following radiative transfer theory, Kd is a function of angular distribution of incident light and water's absorption and backscattering coefficients. Because these optical products are now generated routinely from satellite measurements, it is logical to evolve the empirical Kd to a semianalytical Kd that is not only spectrally flexible, but also the sun‐angle effect is accounted for explicitly. Here, the semianalytical model developed in Lee et al. (2005b) is revised to account for the shift of phase function between molecular and particulate scattering from the short to long wavelengths. Further, using field data collected independently from oligotrophic ocean to coastal waters covering >99% of the Kd range for the global oceans, the semianalytically derived Kd was evaluated and found to agree with measured data within ∼7–26%. The updated processing system was applied to MODIS measurements to reveal the penetration of UVA‐visible radiation in the global oceans, where an empirical procedure to correct Raman effect was also included. The results indicated that the penetration of the blue‐green radiation for most oceanic waters is ∼30–40% deeper than the commonly used euphotic zone depth; and confirmed that at a depth of 50–70 m there is still ∼10% of the surface UVA radiation (at 360 nm) in most oligotrophic waters. The results suggest a necessity to modify or expand the light attenuation product from satellite ocean‐color measurements in order to be more applicable for studies of ocean physics and biogeochemistry.